Attitude and knowledge of family medicine practitioners towards the association between periodontal disease and obesity - Akram, Z.; Abduljabbar, T.; Hanif, A.; Khan, A.; Vohra, F. (Medknow Publications, 2017)
Objectives: To assess the attitude and knowledge of family medicine practitioners (FMPs) towards the association between periodontal disease and obesity. Materials and Methods: A cross-sectional study was performed and a 13-item survey questionnaire was given to FMPs practicing in 12 different teaching hospitals in Karachi, Pakistan. The questions were aimed at exploring the knowledge of FMP's regarding the association of obesity and periodontal disease and their attitude towards the association of obesity and periodontal disease. Chi-square and Spearman co-efficient were conducted to compare subgroups and correlate factors with the knowledge score of FMPs. Results: A total of 314 questionnaires were completed (response rate = 92%). Median age of participants was 41 years and 57% were females. Almost 61% of FMPs answered all the knowledge questions correctly and 64% reported moderate understanding of the association between periodontal health and obesity. Nearly 73% FMPs inquired from obese patients regarding the periodontal disease and more than half (58%) refer patients to a dentist for evaluation. More than half of FMPs perform periodontal disease screening. Nearly all FMPs considered informing obese patients regarding periodontal disease as one of their roles. Conclusions: FMP's play an important role in the early diagnosis, prevention and treatment of periodontal conditions in obese patients. More than two thirds of FMPs showed good knowledge of the association of obesity and periodontal disease. The attitudes of FMPs towards assessing and referring obese patients at a risk of having periodontal disease were reassuring.